2020
DOI: 10.21500/20112084.4480
|View full text |Cite
|
Sign up to set email alerts
|

Social Support and Academic Achievement of Chinese Low- Income Children: A Mediation Effect of Academic Resilience

Abstract: Using nation-wide survey data (N=2328) from China, this study investigates how social support from family, peers, and teachers influence low-income household children’s (from 13 to 15 years old) academic resilience, as well as how academic resilience mediates the relationship between social support and children’s academic achievement. Structural equation modelling was adopted to analyse the data. The results reveal that (1) low-income household children’s family, peer, and teacher support are associated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 49 publications
2
19
0
Order By: Relevance
“…It is also valuable for achieving individual academic achievement. In addition, the results of this study are also supported by research by Fang et al (2020), which reveals that perceived social support from family, peers, and teachers makes a significant contribution to the academic resilience of an individual. Narayan & Onn (2016) also stated that perceived social support from friends and family made a substantial contribution to academic resilience.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…It is also valuable for achieving individual academic achievement. In addition, the results of this study are also supported by research by Fang et al (2020), which reveals that perceived social support from family, peers, and teachers makes a significant contribution to the academic resilience of an individual. Narayan & Onn (2016) also stated that perceived social support from friends and family made a substantial contribution to academic resilience.…”
Section: Discussionsupporting
confidence: 75%
“…Martin (2002) also describes academic resilience as the ability of students to deal with intellectual decline, stress, and pressure in the learning process effectively. Fang et al (2020) revealed that academically resilient individual characters have social competence, problem-solving abilities, independence, and a sense of purpose. Hendriani (2018) also suggests that academic resilience is resilience or resilience felt by individuals in the learning process, which is a dynamic process and reflects an individual's strength and resilience to rise from negative emotional experiences when facing a stressful and challenging situation.…”
Section: Academic Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…Resilience can also be defined as a person's ability to deal with obstacles, stress, and other difficult situations in overcoming academic problems. Resilience has a significant effect on student learning outcomes Layco (2020); Ifeoma & Chinaza (2020;Hong et al, 2020;Unachukwu, 2020;Ifeoma & Chinaza, 2020;Fang et al, 2020;Mwangi at. al., 2018;Ergen & Kanadli, 2017;Johnson et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…In the context of education, resilience is a person's ability to deal with obstacles, stress, and other difficult situations in overcoming academic problems. It, as suggested by a number of researchers, has a positive relationship and influence on learning outcomes (Hong et al, 2020;Unachukwu, 2020;Ifeoma & Chinaza, 2020;Fang et al, 2020;Mwangi at. al., 2018;Ergen & Kanadli, 2017;Johnson et al, 2015).…”
Section: The Effect Of Resilience On Learning Outcomesmentioning
confidence: 98%